DETERMINING THE MOTIVATIONS FOR POLITICAL PARTICIPATION AMONG ELECTED YOUTH LEADERS - Palomares, Perla Piedad; Cadutdut, Doods Edwards; Amod, Al-Farouk; Tomaro, Queenie Pearl Villalon (Jurnal Studi Pemerintahan, 2021)
In the Philippines, Sangguniang Kabataan (SK), an aspect of politics in the local government level provides spaces for youth’s meaningful participation in policy-making and governance. In this study we expand the cast of the domain of motivational studies to provide a new perspective on why youth participate in politics, the extent of their political participation and the relationship of the motivations to their political participation. Findings reveals that in terms of the overall motivations of the SK officials, the SK officials are both intrinsically and extrinsically motivated, but leans more on the intrinsic type of motivation. Although they are both intrinsically and extrinsically motivated, the extrinsic motivation of the SK officials is more highly self-determined. Moreover, results show they have an average to high levels of political participation. Lastly, the relationship between the motivations and political participation was measured. Results show that only the intrinsic motivation has a significant impact to the political participation of the SK officials. This goes to show the importance of Civic Education and Leadership development in developing motivations for leadership and political engagement of the youth.